Temporal bone paragangliomas: 15 years experience - Düzlü,Mehmet (2018)
Abstract Introduction Temporal bone paragangliomas (TBPs) are benign tumors arising from neural crest cells located along the jugular bulbus and the tympanic plexus. In general surgical excision, radiotherapy and wait-and-scan protocols are the main management modalities for TBPs. Objective In this paper we aim to present our clinical experience with TBPs and to review literature data. Methods The patients who were operated for tympanomastoid paraganglioma (TMP) or tympanojugular paraganglioma (TJP) in our clinic in the last 15 years were enrolled in the study. A detailed patient's charts review was performed retrospectively. Results There were 18 (52.9%) cases with TMPs and 16 (47.1%) cases with TJPs, a total of 34 patients operated for TBPs in this time period. The mean age was 50.3 ± 11.7 (range 25-71 years). The most common presenting symptoms were tinnitus and hearing loss for both TMPs and TJPs. Gross total tumor resection was achieved in 17 (94.4%) and 10 (62.5%) cases for TMPs and TJPs, respectively. Five patients (31.2%) with TJP experienced facial palsy following the operation. For all the patients the mean follow-up period was 25.8 months (range 4-108 months). Conclusion In conclusion, based on our findings and literature review, total surgical excision alone or with preoperative embolization is the main treatment modality for TBPs. However radiotherapy, observation protocol and subtotal resection must be considered in cases of preoperative functioning cranial nerves, large tumors and advanced age.